Ranking - a running debate - Razak, Dzulkifli Abd (2011)
LAST week, I was privileged to be on the same side as Professor Malcolm Grant, president and provost of University College, London, in a debate on the subject International World Ranking -- Where Do You Stand? at the Going Global 2011 conference in Hong Kong. Our opponents were two high-profiled rankers, at least to Malaysians, namely the combined Times Higher Education (THE) and QS team.